Upaya Peningkatan Keterampilan Passing Bawah Bola Voli Melalui Metode Drill - Dimas Adi Nugroho; Faridha Nurhayati; Indra Bagus Lesmana (Lembaga Pengembangan Kinerja Dosen, 2024)
This The aim of this research is to find out whether the drill training approach can improve the volleyball passing skills of class VI-D students at SDN Lidah Wetan II/462 Surabaya. The aim of this classroom action research is to improve basic passing technique skills in volleyball. The research population was 30 students, and each student was sampled using the Total Sampling method. Data was collected using the lower passing skills research rubric. The results of the analysis show an increase in volleyball underpassing skills with an average score of 57, so the pre-cycle completion score is 43%. Completeness increased to 60% with an average score of 78 in cycle I. In cycle II, there were 25 students who completed, and the students' completeness score again increased to 83% with an average score of 84.5. These results show the effectiveness of the drill method approach in improving volleyball bottom passing skills